2018
DOI: 10.1186/s12885-018-4731-9
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of blood VEGF kinetics in patients with locally advanced esophageal squamous cell carcinoma receiving curative concurrent chemoradiotherapy

Abstract: BackgroundTo evaluate the role of blood vascular endothelial growth factor (VEGF) kinetics in patients with locally advanced esophageal squamous cell carcinoma (ESCC) receiving curative concurrent chemoradiotherapy (CCRT).MethodsA total of 97 locally advanced ESCC patients were enrolled. All the patients had their blood drawn at three time points to determine their levels of VEGF, including pre-chemotherapy (day 0), post-chemotherapy (day 5), and pre-cycle 2 chemotherapy (day 28). The VEGF levels were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“… 46 The depletion of VEGF was employed for superior clinical outcomes of ESCC during concurrent chemoradiotherapy. 47 VEGF along with its family factors is documented as the central components of abnormal angiogenesis with extensive functionality in a wide variety of tumors and diseases. 22 Mechanically, solid tumors by producing VEGF supply the oxygen and essential nutrients for angiogenesis by producing VEGF, thus making the inhibition of VEGF signaling capable of impairing tumor angiogenesis, to consequently suppress tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“… 46 The depletion of VEGF was employed for superior clinical outcomes of ESCC during concurrent chemoradiotherapy. 47 VEGF along with its family factors is documented as the central components of abnormal angiogenesis with extensive functionality in a wide variety of tumors and diseases. 22 Mechanically, solid tumors by producing VEGF supply the oxygen and essential nutrients for angiogenesis by producing VEGF, thus making the inhibition of VEGF signaling capable of impairing tumor angiogenesis, to consequently suppress tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clinical benefit for patients who experience a significant tumor remission after CCRT, while there is a problem for patients who are not sensitive to CCRT. VEGF kinetics is a prognostic factor for locally advanced ESCC patients receiving CCRT [ 50 ]. Y.H.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with recurrence within 1 year after treatment tended to have lower levels of growth factors. In previous studies, VEGF and EGF have been shown to correlate with worse prognosis in both head and neck cancer and esophageal cancer (2628). A similar connection was not seen in our material.…”
Section: Discussionmentioning
confidence: 91%